Experiment of Instantaneous Crystallization - Ward, Lock (Wonders of electricity and the elements, being a popular account of modern electrical and magnetic discoveries, magnetism and electric machines, the electric telegraph and the electric light, and the metal bases, salt, and acids, 1870)
Illustration depicting an experiment in the instantaneous formation of salt crystals.
Keywords: Scientific illustration; Science--Study and teaching; Science--Experiments; Crystallization